The Relationship Between Elevated Serum Uric Acid and Risk of Stroke in Adult: An Updated and Dose–Response Meta-Analysis - Qiao, Tianci; Wu, Hongyun; Peng, Wei (Frontiers in Neurology, 2021)
Background: Uric acid is proposed as a potential risk factor for stroke in adult, yet the results of published studies are not often accordant. Methods: Literature retrieval, study selection and data extraction were completed independently and in duplicate. Only prospective cohort studies were included. Effect-size estimates are expressed as hazard ratio (HR) and 95% confidence interval (CI). Results: Summary data from 19 articles, involving a total of 37386 male and 31163 female, were meta-analyzed. Overall analyses revealed a remarkably significant association between SUA levels and the risk of total stroke (HR=1.13; 95% CI: 1.09 to 1.18; P<0.001), ischemic stroke (HR=1.15; 95% CI: 1.10 to 1.21; P<0.001), and hemorrhagic stroke (HR=1.07; 95% CI: 1.00 to 1.15; P=0.046). No obvious distinction had been found between ischemic stroke and hemorrhagic stroke. In subgroup analyses, the association of SUA levels and the risk of total stroke was statistically significant in female (HR=1.19; 95% CI: 1.12-1.26; P <.001) and male (HR=1.11; 95% CI: 1.05-1.17; P <.001). Coincidentally, it was also statistically significant for ischemic stroke, both in female (HR=1.26 95% CI: 1.17-1.36; P <.001) and male (HR=1.12; 95% CI: 1.06-1.19; P <.001). But for hemorrhagic stroke, it was only statistically significant in female (HR=1.19; 95% CI: 1.04-1.35; P =.01). Our dose-response research indicated the J-shaped trend between the ascending SUA levels and the higher risk of suffering from stroke. Conclusions: Our findings indicate that elevated SUA is a significant risk factor for adult stroke, both for ischemic stroke and hemorrhagic stroke, and especially in females.